ANALYSIS OF DEFECTS, DAMAGES, AND DEFORMATIONS IN ARCHITECTURAL MONUMENTS AND PROBLEMS IN THEIR RESTORATION - Akhmedov , Barkhayot; Shukurova, Karomat; Utegenova , Mahliya; Saydullayeva, Dildora (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article analyzes the deformations and damages observed in the structures of architectural monuments located in the Republic of Uzbekistan, based on a review of the literature and the results of technical inspections. The defects and deformations in the monuments were identified through visual inspections and instrumental investigations. During the instrumental study, a Faro Focus M70 laser scanner was used. The results of this study can be applied in assessing the technical condition of architectural monuments and performing strengthening work. This research is significant for conducting monitoring, evaluating the technical state of structures, and determining the effectiveness of reinforcement measures.